The Surface Science of Metal Oxides - Henrich V. E Victor E. (New York, Cambridge University Press, 2000)
This book is the first to give a comprehensive account of the fundamental properties of metal-oxide surfaces and their interaction with atoms, molecules and overlayers. It will act as a valuable reference for anyone interested in learning about the surface science of this fascinating class of materials, whose properties span the entire range from metals to semiconductors and insulators. The surfaces of metal oxides are of great technological importance, and play a crucial role in an extremely wide range of phenomena. A detailed knowledge of their properties is central to the investigation of processes such as the environmental degradation of high-Tc superconductors, or in analyzing the nature of the bonding between grains of alumina in sintered ceramics. Metal-oxide surfaces are also of increasing importance in fields such as catalysis, the passivation of metal surfaces, and gas sensing for pollution monitoring and control. As well as giving a general overview of the basic properties of metal oxides, an extensive and thorough compilation of the theoretical and experimental research which has been performed on well-characterized single-crystal oxide surfaces is provided, thus making the book suitable for those graduate students and established researchers in materials science, chemistry, physics or geology who have an interest in metal-oxide surfaces.